THE RELATIONSHIP BETWEEN AGE AND PARITY WITH MYOMA UTERI IN DR. H. SOEWONDO HOSPITAL KENDAL - Dian Kusumaningtyas; Sari Ardiyanti; Norwidya Priansiska; Winda Windiyani (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Myoma uteri is one of benign gynecological tumors are the most common, found one in four women of reproductive age. The incidence of uterine myoma approximately 20-30% of all women. Myoma uteri was not found in children who have not menstruating, in women aged 35-45 years was found about 25% and in menopausal women is only about 10%. Just a little possibility of developing uterine myomas in women often give birth than those who were never pregnant or just had a single pregnancy. Aims: The purpose of this study was to determine the relationship between age and parity of women with myoma uteri. Methods: This research is analytic survey with case control method. The study was conducted at Dr. H. Soewondo Hospitals in Kendal Regency in July 2011. The population of this study were all patients with gynecological diseases are treated in March to July, 2011. Samples taken are saturated sample with accidental sampling method, which is 59 people. Data analysis using Chi-Square test. Results: The analysis showed no relationship between age and uterine myoma (p value> α (0.05)) and there is a relationship between parity with the incidence of uterine myoma (p value <α (0.05)). Conclusion: Further research is needed with the bigger number of samples than this study and the cohort studies may be better for this study.